Analisis Student Well-Being dan Gratitude dengan Perilaku Prososial Siswa di Masa Pandemi Covid-19 - Rinisari, Sulistyo; Sari, Nina Permata; Setiawan, Muhammad Andri (Buletin Konseling Inovatif, 2025)
The pro-social behavior is one of the contributing factors to students’ success in developing society’s healthy social interaction. This study aims to investigate the correlation between students’ collective well-being and gratitude with their pro-social behavior during the COVID-19 pandemic. This study involved eighth grader students of junior high school students. This study used a quantitative approach with a correlational research design. The samples were selected using the total sampling of 201 students, while the data were garnered through the students’ well-being, gratitude, and pro-social behavior scales. The scales were constructed using the Likert scale, distributed online through Google Forms. The data analysis was carried out using product correlation moment through Microsoft Excel and SPSS version 26. Our results showed a positive and significant correlation between students’ well-being with their pro-social behavior, positive and significant correlation between gratitude and pro-social behavior, as well a positive and significant collective relation between students’ well-being and gratitude with their pro-social behavior during the COVID-19 pandemic.